Message of Nationalism in the Music Video 'Wonderland Indonesia' - Teguh Dwi Putranto; Daniel Susilo (Fakultas Ilmu Komunikasi UKWMS, 2021)
Film is a communication medium that includes audio-visual types that are used to convey messages to a group of people watching. In addition to films, music videos which are also a medium of communication also convey messages in an audio visual work. One of the trending music videos during the celebration of the 76th Anniversary of the Republic of Indonesia (HUT RI) in 2021 is